The Wiley Blackwell handbook of childhood social development - Smith, Peter K.; Hart, Craig H. 1957- (Handbooks of developmental psychology, 2014)
This text presents an authoritative and up-to-date overview of research and theory concerning a child's social development from pre-school age to the onset of adolescence. It presents the most up-to-date research and theories on childhood social development and includes comprehensive coverage of a range of disciplinary perspectives